COVID-19 vaccine hesitancy in conflict zones: A review of current literature - Siddiqui, Amna; Priya,; Adnan, Alishba; Abbas, Samina; Qamar, Khulud; Islam, Zarmina; Rahmat, Zainab Syyeda; Essar, Mohammad Yasir; Farahat, Ramadan Abdelmoez (Frontiers in Public Health, 2022)
Background Vaccine hesitancy (VH) is prevalent in conflict zones due to a lack of essential resources and knowledge, thereby escalating the coronavirus disease of 2019 (COVID-19) cases in these territories. This has resulted in a higher incidence of cases from exposure to a single COVID-19 positive case and further burdens the health care system of conflict zones which are already on the brink of collapsing. Aim This narrative review aims to determine VH to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine in five conflict zones that include Somalia, Yemen, Palestine, Syria, and Afghanistan. Methodology A Boolean search was carried out in MEDLINE-PubMed from inception till 6 June 2022. The search was performed by using the following keywords: “(SARS-CoV-2 OR covid OR covid 19) AND (vaccine hesitancy OR covid vaccine acceptance OR intention to vaccinate) AND (Syria OR Yemen OR Palestine OR Afghanistan OR Somalia”). The full text of all relevant articles in English along with their supplementary material was extracted. Results All the included studies reported at least 30% or more increase in vaccine hesitancy among conflict settings. VH was mostly due to a lack of available resources, lack of appropriate knowledge, and believing misleading rumors about the vaccine. Discussion Considering the massive amount of reluctance among people residing in conflict zones, the need to take effective measures against VH is undoubtedly apparent. This can be accomplished by carrying out mass vaccinations by the governments and proper health education through raising the public awareness regarding vaccines, thereby eliminating rumors that exacerbate the fear of adverse effects. Conclusion The approach described in this article to combat VH can be implemented to increase vaccination rates and significantly alleviate R0 across the globe.